Integration of bai salam contracts with erp odoo: Enhancing financial transparency and efficiency in sharia-compliant SMEs - Dicky Octaviano; Amie Amelia (Institute of Accounting Research and Novation (IARN), 2025)
Digital transformation in Sharia-compliant small and medium enterprises (SMEs) is crucial for achieving operational efficiency and financial transparency, particularly in sectors like the garment industry. This paper examines the integration of Bai Salam contracts—a forward sale mechanism in Islamic finance where payment is made upfront for future delivery—into the open-source Enterprise Resource Planning (ERP) system Odoo. Using a qualitative descriptive case study approach supplemented by descriptive statistical analysis, we analyze the implementation at Khanza Maryam, an Indonesian Muslim garment SME. Findings reveal that Odoo's modular features, such as automated accounting and real-time inventory tracking, significantly improve transaction recording transparency, reduce errors by 85%, and boost financial performance ratios from 1.15 to 1.28. Challenges include system customization for Sharia compliance and low digital literacy, addressed through training and feature optimization. This study contributes a practical blueprint for SMEs adopting ERP for Bai Salam transactions, promoting ethical and efficient Islamic financial management.